Design and analysis of a rotating device actuated by shape memory alloy for recovering useful energy from a waste heat source - Han, Yuguang (2018)
The discovery of shape memory effect in materials has enabled the direct conversion of low-grade thermal energy of less than 100°C to mechanical energy. There have been a number of researches on the use shape memory alloys (SMAs) for rotational actuation; however, very few of these researches provided clear insight in identifying the enabling factors for the functionality of such devices. This issue is especially prominent in the previous research, where a rotating device actuated by Nitinol was fabricated, but failed to function as expected. This project builds on the aforementioned research and identifies the critical factors that enable the functionality of the rotational device by performing extensive analysis and experimentation. A selection of optimising factors for the device are discussed based on the observations from the experiments. In this process, the prototype from the previous research is modified based on these conclusions, and eventually becomes functional. The device is then redesigned to fully incorporate the modifications made. This report of the project first presents a brief review of existing literature on the subject, followed by relevant theories on the functionality of the device. The relevant simulations, experiments as well as modifications performed on the device, complete with their observations and findings, are then documented. The redesign of the device is then presented after a summary of the observations and findings.